Jump kinetic determinants of sprint acceleration performance from starting block in male sprinters - Maulder, P. S.; Bradshaw, E. J.; Keogh, J. (Journal of Sports Science & Medicine, 2006)
The purpose of this research was to identify the jump kinetic determinants of sprint acceleration performance from a block start. Ten male (mean ± SD: age 20 ± 3 years; height 1.82 ± 0.06 m; weight 76.7 ± 7.9 kg; 100 m personal best: 10.87 + 0.36 s {10.37 - 11.42}) track sprinters at a national and regional competitive level performed 10 m sprints from a block start. Anthropometric dimensions along with squat jump (SJ), countermovement jump (CMJ), continuous straight legged jump (SLJ), single leg hop for distance, and single leg triple hop for distance measures of power were also tested. Stepwise multiple regression analysis identified CMJ average power (W/kg) as a predictor of 10 m sprint performance from a block start (r = 0.79, r2 = 0.63, p<0.01, SEE = 0.04 (s), %SEE = 2.0). Pearson correlation analysis revealed CMJ force and power (r = -0.70 to -0.79; p = 0.011 - 0.035) and SJ power (r = -0.72 to -0.73; p = 0.026 - 0.028) generating capabilities to be strongly related to sprint performance. Further linear regression analysis predicted an increase in CMJ average and peak take-off power of 1 W/kg (3% & 1.5% respectively) to both result in a decrease of 0.01 s (0.5%) in 10 m sprint performance. Further, an increase in SJ average and peak take-off power of 1 W/kg (3.5% & 1.5% respectively) was predicted to result in a 0.01 s (0.5%) reduction in 10 m sprint time. The results of this study seem to suggest that the ability to generate power both elastically during a CMJ and concentrically during a SJ to be good indicators of predicting sprint performance over 10 m from a block start.